PENGARUH ORIENTASI PASAR TERHADAP KUALITAS LAYANAN DAN KEUNGGULAN BERSAING - Andini Andini; Junaidi Junaidi (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
In hyper competitive environment, market orientation is not only absolutely necessary for corporations but also for nonprofit organizations such as Madrasah education organization. Hence, this study aims to explain the effect of market orientation on service quality of Madrasah and competitive advantage. Data analysis used structural equation modeling (SEM) to examine the hypothesis. Unit analysis consists of 160 students and parents of Madrasah Aliyah Negeri. Based on data analysis result all goodness-of-fit criteria can be fulfilled, so it’s concluded that market orientation has significant effect on service quality and competitive advantage. But the model reveals that service quality has no significant effect on competitive advantage.